The impact of Pr and Nd substitution on structure, hysteresis and magnetocaloric properties of La1−x(Pr, Nd)xFe11.6Si1.4. (15th March 2021) - Davarpanah, Amin; Radulov, Iliya; Shayanfar, Navid; Maccari, Fernando; Skokov, Konstantin; Amaral, Joao; Gutfleisch, Oliver
Abstract: In this study, a combination of induction melting and suction casting methods were used to produce a series of high-purity samples of L a 1 − x R x F e 11.6 S i 1.4 system with R = Pr and Nd for x = 0.1, 0.2, 0.3 and 0.4. The Curie temperature ( T C ) is lowered for all the substituted compositions compared to L a F e 11.6 S i 1.4, while the hysteresis area shows a small increase for higher amounts of substitution element. The estimated isothermal magnetic entropy change ( Δ S T ) of all samples are in the same range with a maximum of 25  J k g − 1 K − 1 . The Δ T a d, under the cyclic conditions for all compositions decreases compared to the first application of the magnetic field due to the thermal hysteresis. Applying the Bean–Rodbell model to the isothermal magnetization data, the temperature dependence of the critical field was found. Excluding the phase transition region, the model accurately describes the temperature and field dependence of magnetization above and below the magnetic transition, highlighting the magnetic moment change of the system due to the structural transformation.